Pemanfaatan Library Zxing Sebagai Pembaca Barcode pada Aplikasi Sistem Inventory Toko Pakaian - Rahmadani, Dandi; Aulia, Rachmat (Universitas Harapan Medan, 2022)
Rapidly developing applications have provided enermous benefits for small and medium enterprises activities such as clothing stores. Therefore we need a good inventory system in a clothing store. In this study, the author will design an android-based inventory application system that will be implemented in a clothing store. This applications was built by utilizing a mobile device as a media processing clothing inventory system. This application will utilize the android device’s camera as a barcode scanner or barcode reader. So that, all sales transactions will be done through a barcode scanner. Where the barcode image will be generated automatically based on the id of the clothes. With this applications, it will be easier for the clothing shop owner to process their clothing inventory system because all the processes are carried out in one android-based smartphone device. In implementation, this application will utilize the Zxing library as a function of distrbuting barcodes on smartphone devices.